Antiproliferative and Morphological Analysis Triggered by Drugs Contained in the Medicines for Malaria Venture COVID-Box Against Toxoplasma gondii Tachyzoites - Andréia Luiza Oliveira Costa; Mike dos Santos; Giulia Caroline Dantas-Vieira; Rosálida Estevam Nazar Lopes; Rossiane Claudia Vommaro; Érica S. Martins-Duarte (Microorganisms)
Toxoplasma gondii is a protozoan, and the etiologic agent of toxoplasmosis, a disease that causes high mortality in immunocompromised individuals and newborns. Despite the medical importance of toxoplasmosis, few drugs, which are associated with side effects and parasite resistance, are available for its treatment. Here, we show a screening of molecules present in COVID-Box to discover new hits with anti-T. gondii activity. COVID-Box contains 160 molecules with known or predicted activity against SARS-CoV-2. Our analysis selected 23 COVID-Box molecules that can inhibit the tachyzoite forms of the RH strain of T. gondii in vitro by more than 70% at 1 µM after seven days of treatment. The inhibitory curves showed that most of these molecules inhibited the proliferation of tachyzoites with IC50 values below 0.80 µM; Cycloheximide and (-)-anisomycin were the most active drugs, with IC50 values of 0.02 μM. Cell viability assays showed that the compounds are not toxic at active concentrations, and most are highly selective for parasites. Overall, all 23 compounds were selective, and for two of them (apilimod and midostaurin), this is the first report of activity against T. gondii. To better understand the effect of the drugs, we analyzed the effect of nine of them on the ultrastructure of T. gondii using transmission electron microscopy. After treatment with the selected drugs, the main changes observed in parasite morphology were the arrestment of cell division and organelle alterations.